Obtenção e Caracterização do Extrato Seco Padronizado dos Frutos da Sucupira Pterodon emarginatus Vogel, Fabaceae - OLIVEIRA, Patrícya Caixeta de (2010)
The Pterodon emarginatus Vogel, known as sucupira branca (Fabaceae) has been shown to possess larvicidal activity against (Aedes aegypti), antiparasitic effect (Leishmania amazonensis), fungicide, bactericide, antioxidant, antiinflammatory, antinociceptive, and antiproliferative activity among several different human cancer cell lines that may be related to presence of diterpenes, in particular, vouacapanes derivatives. This work aimed to define and characterize the powder, the crude and standardized dry extract of the fruit of sucupira . After crushing the fruits, showed 1.2% volatile. The chromatographic (TLC) indicated the presence of chemical markers vouacapanes (6α,7β-dihydroxyvouacapan-17β-oic acid - Rf = 0.16; 6α,7β-dihydroxyvouacapan-17β-oate methyl ester - Rf = 0.44; 6α-hydroxyvouacapan-7β-17β-lactone - Rf = 0.71) and lupeol (Rf = 0.78). In vibration bands in the infrared region coinciding with the five main bands of vouacapanes (-OH, C-H , C=O, C=C, C-O). The concentration of total terpenes of 9.3%. Then to obtain the crude extract was held percolation in 95% ethanol PA. The crude extract showed pH 5.1, relative density of 0.87, viscosity of 25.43 mPas, solid 15.2%, total terpenes of 17.1% and the same chromatographic profile and in the infrared spectrum obtained for the powder plant. Another method used for investigation of terpenes was the gas chromatography / mass spectrometry in the hexane extract. We identified the presence of vouacapanes and the lupeol. The drying process of the crude extract was used nebulization (spray drying) using different adjuvants drying, flow of 0.19 L / h, air flow 35 L / min, inlet temperature 110°C, outlet temperature 97°C, double fluid nozzle spray type 1.2 mm. The best results were obtained with the colloidal silicon dioxide (Aerosil®) to 20%, giving an appearance of fine powder. Thermal analysis performed for the marker 6α,7β-dihydroxyvouacapan-17β-oate methyl ester showed that the drying parameters were safe by preventing the thermal degradation of diterpenes. The efficiency of the drying process was 16.2%, degradation of 10.9% and the concentration of terpenes total in dry extract was 13.9%. The chromatographic profile was maintained and the volatile content was 3.5%. The photomicrographs showed irregular and spherical particles, rough surface. The analytical method by spectrophotometry in the visible region for the quantification of total terpenes in the dust, crude extract and dry extract was validated presenting selective, linear, precise, accurate and robust. In the test of antinociceptive activity (capsaicin), the pre-treatment with dry extract of sucupira (SDE 1000 mg / kg + 20% DMSO) reduced the time reactivity in 50.9% compared to the vehicle. The results may suggest that the technological processes employed to transform the fruits of sucupira in standardized dry extract was adequate to maintain quality chemistry and antinociceptive activity described for the fruits. This work represents the first description of the taking of standardized dry extract and identification of lupeol in fruits of sucupira .